(untitled) (The International Journal for Scientific Research, 2026)
The current study aims to investigate the effectiveness of school administration in utilizing educational platforms from the perspective of female teachers in the Wilayat of Sohar. A descriptive research method was applied, as it aligns with the nature and objectives of the study. The study sample consisted of 250 female teachers from Sohar randomly during the second semester of the 2024/2025 academic year. To collect data, a google form questionnaire was created that comprised two main dimensions: the first focused on the effectiveness of school administration in planning for the use of digital educational platforms, and the second addressed the effectiveness of school administration in monitoring and regulating teaching and learning processes. The study tool included 30 items, and reliability analysis showed a high internal consistency with Cronbach’s alpha coefficient of 0.955. The findings showed that the effectiveness of school administration in utilizing educational platforms, from the perspective of female teachers in Sohar, was rated as high. Furthermore, the findings revealed no statistically significant differences at the α ≤ 0.05 level attributable to the variables of educational cycle or years of experience. Based on these results, the study recommends enhancing the role of school administration by developing their digital and administrative skills related to the integration of technology in the educational process. It also emphasizes the importance of providing ongoing training programs for administrators and teachers to strengthen their capabilities in effectively using educational platforms. Additionally, the study highlights the need to improve the technical infrastructure within schools to create an environment conducive to seamless technology integration. The study also suggests conducting future research that includes other Wilayats and educational levels, with a particular focus on evaluating the impact of digital platform utilization on students’ academic achievement and performance.